Comparison of a New Gold Immunochromatographic Assay for the Rapid Diagnosis of the Novel Influenza A (H7N9) Virus with Cell Culture and a Real-Time Reverse-Transcription PCR Assay. (14th April 2014) - Jin, Changzhong; Wu, Nanping; Peng, Xiaorong; Yao, Hangping; Lu, Xiangyun; Chen, Yu; Wu, Haibo; Xie, Tiansheng; Cheng, Linfang; Liu, Fumin; Kang, Keren; Tang, Shixing; et al.
Abstract : We assessed a colloidal gold immunochromatographic assay (GICA) for rapid detection of influenza A (H7N9) and compared it with reverse-transcription-polymerase chain reaction (RT-PCR) and viral culture. Samples from 35 H7N9 infected patients were collected, including 45 throat swab samples, 56 sputum samples, and 39 feces samples. All samples were tested by GICA, viral culture, and RT-PCR. GICA specifically reacted with recombinant HA proteins, virus lysates, and clinical samples from H7 subtype viruses. Compared with RT-PCR, GICA demonstrated low sensitivity (33.33%) but high specificity (97.56%). The positive rate of GICA tests for samples collected in the period from 8 to 21 days after contact with poultry was much higher than those for samples collected before or after this period. Compared with viral culture, GICA showed sensitivity of 91.67% and specificity of 82.03%. Sputum specimens were more likely to test positive for H7N9 virus than samples from throat swabs and feces. The GICA-based H7 test is a reliable, rapid, and convenient method for the screening and diagnosis of influenza A (H7N9) disease, especially for the sputum specimens with high viral load. It may be helpful in managing H7N9 epidemics and preliminary diagnosis in early stages in resource-limited settings.